Overview of Urine Cylinders in Patients With Pulmonary Tuberculosis Undergoing Advanced First-Line Treatment at the RSUD Ciamis - Nurhalimah, Sinta; Farihatun, Atun; Kania Yulianti, Dewi; Istianah, Euis (Mukhtabar Journal of Medical Laboratory Technology, 2024)
Background & Objective: Pulmonary tuberculosis is a contagious disease caused by Mycobacterium tuberculosis bacteria that can attack various organs, especially the lungs. Tuberculosis patients are treated with anti-tuberculosis drugs such as rifampicin and streptomycin, which can potentially cause kidney function impairment. To detect any abnormalities in the kidneys, a urine sediment examination is conducted, which can identify an increase in urine cylinders if any damage to the kidneys is present. This study aims to provide insights into urine cylinders in patients with pulmonary tuberculosis based on the duration of their treatment. Method: This is a descriptive study that utilised a purposive sampling technique. The study involved 38 Tuberculosis patients as respondents. Sampling was carried out at the DOTS clinic of RSUD Ciamis and the research was conducted between October 2021 and May 2022. Result: Out of 38 samples, 6 people tested positive for cylinders at a value of +1 (which means very little). These cylinders included hyaline, wax, granule, fat, and epithelial cell cylinders. The percentage of people who tested positive for cylinders was 15.8%. On the other hand, 32 people tested negative for cylinders, which accounts for 84.2% of the total sample. Conclusion: It can be concluded that cylinders were found in tuberculosis patients. Future researchers are advised to examine urine cylinders in pulmonary tuberculosis patients undergoing the sixth month of treatment in patients at a young age.